2020
DOI: 10.3389/fmicb.2020.00396
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Metabolic Pathway Difference Between Saccharopolyspora pogona and Saccharopolyspora spinosa by Comparative Proteomics and Metabonomics

Abstract: Butenyl-spinosyn, a secondary metabolite produced by Saccharopolyspora pogona, exhibits strong insecticidal activity than spinosyn. However, the low synthesis capacity and unknown metabolic characteristics of butenyl-spinosyn in wild-type S. pogona limit its broad application and metabolic engineering. Here, we showed that S. pogona exhibited increased glucose consumption ability and growth rate compared with S. spinosa, but the production of butenyl-spinosyn was much lower than that of spinosyn. To further el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…The side chain groups of butenyl-spinosyn are easily modified to generate many derivatives, and more than 30 derivatives have been isolated and identified so far [ 4 ]. However, the low yield of wild-type butenyl-spinosyn under natural conditions hinders its industrial production and application [ 8 , 9 ]. Initially, culture media optimization, physical or chemical mutagenesis, and gene rearrangement have been used to explore the potential productivity of secondary metabolites from Streptomyces [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The side chain groups of butenyl-spinosyn are easily modified to generate many derivatives, and more than 30 derivatives have been isolated and identified so far [ 4 ]. However, the low yield of wild-type butenyl-spinosyn under natural conditions hinders its industrial production and application [ 8 , 9 ]. Initially, culture media optimization, physical or chemical mutagenesis, and gene rearrangement have been used to explore the potential productivity of secondary metabolites from Streptomyces [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have been conducted on the metabolic pathways and regulatory mechanisms of butenyl-spinosyn biosynthesis [ 14 ]. Genome sequencing comparison has revealed that the PKS gene in the butenyl-spinosyn biosynthetic gene cluster is very similar to spinosyn (91%–94%), and there are many similarities in their biosynthetic and metabolic pathways [ 8 ].The main difference is that of the 5 functional domains encoded by busA in the butenyl-spinosyn gene cluster, a butenyl group replaces the ethyl group at position C21 [ 15 , 16 ]. Short-chain acyl-CoAs, such as acetyl-CoA, malonyl-CoA, methylmalonyl-CoA and propanoyl-CoA, are important precursors for the synthesis of many polyketide secondary metabolites, including butenyl-spinosyn [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, though lots of studies such as proteomics and metabolomics have been done on spinosyns biosynthesis process, the linkage between spinosyns formation and primary metabolism network still remained un-revealed 32 36 . In this study, we try to find out the different metabolism processes in wild-type strain S. spinosa ATCC_49460 and spinosad high-yield strain S. spinosa S3-3.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the key steps in spinosad biosynthesis of S. spinosa, the most commonly used reference gene was DNA polymerase sigma factor subunit A (sigA) [15][16][17]. Also, 16S rRNA was selected as the reference gene for revealing the metabolism difference between Saccharopolyspora pogona and S. spinosa, as well as seeking the link between primary metabolism and spinosad biosynthesis [18,19]. And ribosome protein L13 (rbL13) was also selected to determine the transcript levels of rex, ctyA and ctyb, which were related to the redox control in S. spinosa [20].…”
Section: Introductionmentioning
confidence: 99%